(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The majority of Baghdad region’s problems are related to building contraventions, which have increased dramatically after the event in 2003 and the intense immigration from other parts of the country to Baghdad. These events coincided with a boom in the construction section and increased in density selling by Baghdad municipality. Due to the long-term consequence of this phenomenon and the inefficient and inappropriate of municipality actions, it is very important to identify the main causes of these malpractices so that we can develop the solutions for it. The research examined the causes of these violation, which include the contraventions of height, setback and plot coverage. Through reviewing the literature review and questioner, the following indicators were examined: level of awareness, violation of regulations to meet housing needs, violation of legislation for purpose of profitability, income of owners, supervision. The survey sample was answered by 100 household, Pearson correlation used to achieve accuracy of the causes of building contraventions . The results revealed that the level of awareness , income level are the main reasons of building contraventions .